2022
DOI: 10.53790/ajmss.v3i2.46
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Communication, and Poverty Alleviation in Nigeria: Prospects and Challenges

Abstract: Poverty is a prevalent global developmental challenge recognised by the United Nations (UN) as part of the Sustainable Development Goals (SDG) and the desire to eradicate it is identified as goal number one (No Poverty). The challenges and setbacks to achieving poverty alleviation in Nigeria are multifaceted, including political, economic, and in some cases communication-related. Communication plays a role in promoting knowledge, social inclusion, and national development programmes. Consequently, where there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Low resources definitely lead to low wages, which causes unfortunate fate or standard of living. Media development theory should be adopted as the base of media participation in poverty eradication programs, so that every country who has this program should have a separate budget allocation as a means of strategy to implement communication for poverty eradication programs (Johnson, Akintayo and Victor, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low resources definitely lead to low wages, which causes unfortunate fate or standard of living. Media development theory should be adopted as the base of media participation in poverty eradication programs, so that every country who has this program should have a separate budget allocation as a means of strategy to implement communication for poverty eradication programs (Johnson, Akintayo and Victor, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Ikem, U. Victor, Akiyanto, and B. Johnson (2022) observed that poverty eradication program in Nigeria was impeded by both political and economic obstacles, and in some cases by poor public policy communication. Therefore, public policy communication plays a crucial role for the successful implementation of various poverty alleviation programs.…”
Section: Introductionmentioning
confidence: 99%
“…It underscored the pivotal role of mass media, including print and electronic media, in improving the lives of the rural poor, and revealed a significant link between unemployment and rural poverty. Furthermore, Ikem and Akintayo (2022) explored communication and poverty alleviation, emphasizing the prevalence of poverty in Nigeria, as characterized by various challenges, including communication-related impediments. Their study underscored the role of communication in promoting knowledge, social inclusion, and national development programs, calling for innovative communication strategies to eradicate extreme poverty by 2030.…”
Section: Existing Research On Media and Poverty In Nigeriamentioning
confidence: 99%
“…The study was conducted in North-Western Nigeria, covering the three most populous states in the region (Kano, Kaduna, and Katsina), with the highest prevalence of MDR-TB and economic deprivation. Nigeria has a GDP per capita of US $2,065.7 (Basak, et al, 2022) and unequal wealth distribution, with about 50% of the 200 million Nigerian population living below the international poverty line of $1.90 per day (Ikem and Akintayo, 2022).…”
Section: Study Settingsmentioning
confidence: 99%